Reconceptualizing Assessment in Islamic Education: A Critical Review of Madrasah Evaluation Practices in the 21st Century - Fatmawati, Erma (Journal of Quality Assurance in Islamic Education (JQAIE), 2025)
This research aims to recontextualize the concept of assessment in Islamic education, particularly in madrasah institutions, to align with 21st-century demands. Using a library research approach, this study critically examines academic literature, educational policies, and the results of previous studies on the evaluation of learning in madrasas. The analysis used thematic and reflective synthesis to identify conceptual gaps and opportunities for developing a more comprehensive assessment model. The results of the study show that assessment practices in madrassas are still dominated by a cognitive approach and by the measurement of learning outcomes oriented toward memorization. The affective, spiritual, and social dimensions have not received adequate attention in the evaluation system. This condition underscores the urgent need to build an integrative, holistic, and Islamic-values-based assessment paradigm. Assessment is not only a tool for measuring academic achievement but also a means of building students’ character, morals, and spiritual awareness. This study emphasizes that recontextualizing madrasah assessments is a strategic step toward improving the quality of Islamic education. The theoretical implications lie in strengthening the concept of value-based evaluation, while the practical implications encourage teachers and educational institutions to develop assessment models that are humanistic and oriented towards the formation of human beings.